Expansão das fronteiras da educação na ciência da informação: a formação de profissionais para atuação no contextos dos dados de pesquisa - Gracielle Mendonça Rodrigues Gomes (2019)
The problems currently faced by scientific institutions in managing and curating research data offer information professionals an attractive opportunity to redefine their roles in supporting research and developing relationships closer to the community. However, there is a substantial lack of courses and training programs being offered by the Information Science Schools for the training of these professionals. Due to this context, the general objective of the research was to develop curricular guidelines that support professional training projects in the field of management and curation of research data pertinent to IS field. The literature review presents, the foundations and practices regarding curriculum development in higher education were presented; the transformations in the scientific communication system and the new paradigms of science; services and skills of research data professionals; and the education of data professionals from the point of view of IS. Regarding the methodology, the research was characterized as qualitative, exploratory and applied. The sample consisted of 95 iSchools, located in 25 countries and distributed on five continents. The data collection was done through documentary research and subdivided into four stages. The data analysis was performed through content and comparative analysis methods and subdivided into five stages. Results show data courses with various focuses and objectives with influences in the curricula of several areas such as Computer Science, Information Science, Statistics, Mathematics, Administration, Communication and Political Sciences; scarcity of data courses directed to the context of research data because most courses are generalist; the training directed, mainly, to the graduate students and professionals, in person or online; and the creation of emphases or concentrations in undergraduate and graduate courses stricto sensu in the data area as a recurrent strategy for insertion of the training in Information Science Schools. In addition, a typology of what composed of 18 thematic axes, 72 thematic sub-axes and 543 skills pertaining to the activities of data professionals, in general, and a matrix of competences was created consisting of 12 thematic axes, 32 thematic sub-axes, 328 competencies and 181 disciplines related to the training of professionals for the management and curation of research data from the perspective of IS to guide curricular projects. Conclusion reiterate the need for more Information Science Schools to provide instruction to help students and professionals to deal with new activities and ways of manipulating research data; a need for IS professors and professionals to open up to learn new knowledge and to carry out activities in the data environment involving Statistics and Computing; and the call for IS professionals, interested in what their role in the future of science to seek the skills and competencies that will give them a crucial role in institutions to support the management and curation of research data.